2019
DOI: 10.1038/s41398-019-0385-x
|View full text |Cite
|
Sign up to set email alerts
|

Computerized multi-domain cognitive training reduces brain atrophy in patients with amnestic mild cognitive impairment

Abstract: The present study aimed to explore the effect of computerized multi-domain cognitive training (MDCT) on brain gray matter volume and neuropsychological performance in patients with amnestic mild cognitive impairment (amnestic MCI). Twenty-one patients with amnestic MCI participated in a computerized MDCT program. The program targeted a broad set of cognitive domains via programs focused on reasoning, memory, visuospatial, language, calculation, and attention. Seventeen Participants completed the intervention a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 61 publications
1
30
0
Order By: Relevance
“…In addition to the within-subject analysis quantifying network alterations after intervention, we also analyzed statistically network alterations at the group-level by defining a new measure, the reorganization index (RI). In this case too, we found that a large number of ROIs were affected after intervention (Fig 8), and these changes at the system/community level (Fig 9) were comparable to the ones we obtained with the within-subject analysis in Fig 7B. Taken together, our results using two different approaches (MG2G and node2vec) and two different methods of analysis (top-15 ROI and t-test) showed consistency in the regions affected by the MDCT intervention, with details of each region presented in S2 Table in Supporting Information. In addition to fMRI networks, in previous work [4] we have investigated the MDCT intervention effects on structural MRI data and found significant increases in gray matter volume in the right angular gyrus and other subareas following the MDCT intervention. In the current study, we further investigated the underlying MDCT intervention effects at both ROI-level and community-level on the fMRI networks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the within-subject analysis quantifying network alterations after intervention, we also analyzed statistically network alterations at the group-level by defining a new measure, the reorganization index (RI). In this case too, we found that a large number of ROIs were affected after intervention (Fig 8), and these changes at the system/community level (Fig 9) were comparable to the ones we obtained with the within-subject analysis in Fig 7B. Taken together, our results using two different approaches (MG2G and node2vec) and two different methods of analysis (top-15 ROI and t-test) showed consistency in the regions affected by the MDCT intervention, with details of each region presented in S2 Table in Supporting Information. In addition to fMRI networks, in previous work [4] we have investigated the MDCT intervention effects on structural MRI data and found significant increases in gray matter volume in the right angular gyrus and other subareas following the MDCT intervention. In the current study, we further investigated the underlying MDCT intervention effects at both ROI-level and community-level on the fMRI networks.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, non-pharmacological cognitive intervention for patients at early stages of AD has received a lot of attention due to its non-invasive manner, safety and scalability. Recent studies show that non-pharmacological cognitive intervention can play a positive role in delaying the process or even reducing the cognitive decline for both healthy controls [3] and amnestic mild cognitive impairment (aMCI) patients [4]. In particular, aMCI is a vital prodromal state of AD harboring memory impairment and has a high risk to progress into AD [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the quadratic surfaces comprising the core of CURATE.AI have been implemented in drug combination discovery platforms to aid in narrowing expansive drug libraries, find the most efficacious combinations from a large parameter space (e.g., dose ranges), and even elucidate and understand the relationships of underlying mechanisms within in vivo and in vitro systems of interest representative of various oncological and infectious disease indications, such as multiple myeloma and tuberculosis. Multiple studies have shown the efficacy of cognitive training delivered in a digital form, that is, to assess dementia state, [44] slow down progression of amnestic mild cognitive impairment, [45] and eventually remediate agerelated deficits in cognitive control. CURATE.AI does not rely on synergy prediction between the various inputs in order to globally optimize intervention.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we focused on functional brain network analysis for aMCI patients, who completed a multi-domain cognitive training (MDCT) intervention that was designed at the PKU-sixth hospital of China. For each of 12 patients, resting-state functional MRI scans and cognitive assessment scores (MMSE 10 and MOCA 11 ) were collected before and immediately after a 12-week intervention 4 . Aiming to investigate quantitatively the underlying functional brain network changes associated with the MDCT intervention, we propose a new approach based on an unsupervised Gaussian embedding-based functional brain network analysis for resting state fMRI data.…”
mentioning
confidence: 99%